Distinctive Features of the Human Marginal Zone and Cajal–Retzius Cells: Comparison of Morphological and Immunocytochemical Features at Midgestation - Tkachenko, Lyubov A.; Zykin, Pavel A.; Nasyrov, Ruslan A.; Krasnoshchekova, Elena I. (Frontiers in Neuroanatomy, 2016)
Despite a long history of research of cortical marginal zone (MZ) organization and development, a number of issues remain unresolved. One particular issue is the problem of Cajal–Retzius cells (C–R) identification. It is currently based on morphology and Reelin expression. The aim of this research is to investigate MZ cytoarchitectonics and Reelin-producing cells morphotypes in the superior temporal, pre- and postcentral cortex at GW24–26. We used Reelin (Reln) as the marker for C–R cells and microtubule-associated protein 2 (MAP2) and neurofilament heavy chain protein (N200) as markers of neuronal maturation. The MZ of all of the investigated areas had the distinct cytoarchitectonic of alternating cell sparse (MZP, SR) and cell dense (SGL, DGL) layers. The distribution of the neuromarkers across the MZ also showed layer specificity. MAP2-positive cells were only found in the SGL. N200 and Reelin-positive neurons in the MZP. N200-positive processes were forming a plexus at the DGL level. All of the N200-positive neurons found were in the MZP and had distinctive morphological features of C–R cells. All of the N200-positive neurons in MZ were also positive for Reelin, whereas MAP2-positive cells lack Reelin. Thus, the joint use of two immunomarkers allowed us to discern the C–R cells based on their morphotype and neurochemistry and indicate that the Reelin-positive cells of MZ at 24–26 GW were morphologically C–R cells. In the current study, we identified three C–R cells morphotypes. Using a 3D reconstruction, we made sure that all of them belonged to the single morphotype of triangular C–R cells. This approach will allow future studies to separate C–R cells from other Reelin-producing neurons which appear at later corticogenesis stages. In addition, our findings support the assumption that a plexus could be formed not only with C–R cells processes but also possibly by other cell processes by the poorly researched DGL, which is only allocated as a part of the human MZ.